Proteostasis and neurodegeneration: a closer look at autophagy in Alzheimer's disease - Barmaki, Haleh; Nourazarian, Alireza; Khaki-Khatibi, Fatemeh (Frontiers in Aging Neuroscience, 2023)
Alzheimer's disease (AD) is characterized by the accumulation of misfolded amyloid-beta and tau proteins. Autophagy acts as a proteostasis process to remove protein clumps, although it progressively weakens with aging and AD, thus facilitating the accumulation of toxic proteins and causing neurodegeneration. This review examines the impact of impaired autophagy on the progression of AD disease pathology. Under normal circumstances, autophagy removes abnormal proteins and damaged organelles, but any dysfunction in this process can lead to the exacerbation of amyloid and tau pathology, particularly in AD. There is increasing attention to therapeutic tactics to revitalize autophagy, including reduced caloric intake, autophagy-stimulating drugs, and genetic therapy. However, the translation of these strategies into clinical practice faces several hurdles. In summary, this review integrates the understanding of the intricate role of autophagy dysfunction in Alzheimer's disease progression and reinforces the promising prospects of autophagy as a beneficial target for treatments to modify the course of Alzheimer's disease.